The value of minor architectures: The hydraulic mills of the Parque Natural Sierra de Grazalema in Sierra de Cádiz - Ramos Carranza, Amadeo; Rivero-Lamela, Gloria (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
The productive rural architectures combine cultural relevance and tradition, although at present they are considered minor architectures and they remain inactive or in ruins. This is the case of the hydraulic mills of the Parque Natural Sierra de Grazalema which have been left out of the valuation and the official protection by Administrations. Valuing these architectures is the general objective of the paper. For it, we start with a geographic, historical and heritage study of the Sierra de Cádiz (the region in which the Parque Natural is located). We continue with the analysis and location of the mills architectures in the Parque Natural Sierra de Grazalema to know more about these hydraulic engineering works. From the idea of "foundation of craftsmanship" proposed by Richard Sennett in The craftsman, the investigation is completed with an analysis of the location of the mills and their interaction with the physical environment, the questions about the influence of rural buildings on other 20th Century architectures for, finally, to open up other types of values that, together with the heritage ones, have hydraulic mills and can lead to possible protection and reactivation actions.